2016
DOI: 10.21831/economia.v12i2.11775
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Etika Bisnis Dan Religiusitas Terhadap Persepsi Etis Mahasiswa Akuntansi

Abstract: Abstrak: Pengaruh Pendidikan Etika Bisnis dan Religiusitas Terhadap Persepsi Etis Mahasiswa Akuntansi. Penelitian ini bertujuan melihat hubungan antara pendidikan etika, gender, religiusitas, dan performa akademik terhadap persepsi etis mahasiswa. Penelitian ini juga ingin membuktikan perbedaan persepsi antara mahasiswa yang sudah atau sedang mengambil mata kuliah etika bisnis dan yang belum, antara mahasiswa laki-laki dan perempuan, serta mahasiswa dengan IPK ≥ 3,3 dan <3,3. Metode analisis data yang digun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 6 publications
3
12
0
9
Order By: Relevance
“…Business must be operated in accordance with the rules of regulation, legislation, politics, economy, social and ethics (Wati & Sudibyo, 2016). Ethical values must be enforced to reduce the occurrence of problems and disadvantages for various parties (Yeltsinta & Fuad, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Business must be operated in accordance with the rules of regulation, legislation, politics, economy, social and ethics (Wati & Sudibyo, 2016). Ethical values must be enforced to reduce the occurrence of problems and disadvantages for various parties (Yeltsinta & Fuad, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Religiosity represents a strong adherence to the value of goodness in a person's religion. Both religion and belief in God have rules for behaving ethically in various aspects of life, including those in the business world (Wati & Sudibyo, 2016). The principles of religion underlie ethical values in work and in doing business.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian ini mendukung penelitian sebelumnya, (Wati & Sudibyo, 2017), religiusitas mempunyai pengaruh terhadap presepsi etis. Artinya semakin rendah religiusitas setiap individu maka semakin besar kemungkinan akan melakukan kecurangan pajak.…”
Section: Hasil Dan Pembahasan Gambaran Umum Objek Penelitianunclassified
“…Because every attitude and action will be accounted for to God. Weibe and Fleck (1980) in Wati and Sudibyo (2016) found that someone who accepts religion as the main focus of their lives tends to have attention to higher moral standards, discipline and responsibility than those who are not religious.…”
Section: Islamic Religiosity In Maintaining the Auditor's Professionamentioning
confidence: 99%